Genomic identification of Toxic shock syndrome producing and methicillin resistant Staphylococcus aureus strains in human and sheep isolates - MOKHTARI, A.; EBRAHIMI KAHRIZSANGI, A.; HASANI, P. (Journal of the Hellenic Veterinary Medical Society, 2018)
Disease-associated Staphylococcus aureus strains often promote infections by producing potent protein toxins such as toxic shock syndrome toxin (TSST). The mecA gene allows a bacterium to be resistant to antibiotics such as methicillin, penicillin and other penicillin-like antibiotics. The aim of this study was to determine the prevalence of Staphylococcus aureus strains producing these two genes. In this study, within 110 cases isolated in Chaharmahal and Bakhtiari province, Staphylococcus aureus was isolated by microbiological methods. Then PCR was done for 66 samples to identify the mecA and TSST-1 genes. The results showed within 30 samples of human skin infection 18 cases (60%) were MRSA and 5 samples (16.66%) were positive for TSST-1 gene. Within 36 samples of ewe subacute mastitis 10 samples (27.77%) and 5 (13.88%) had mecA and TSST-1 genes respectively. Therefore the prevalence of methicillin resistance and toxic shock syndrome producing Staphylococcus aureus isolates was significant in Chaharmahal and Bakhtiari. Due to the presence of these isolates in Iran and their threatening role in public health, more attention for their monitoring and treatment is essential.